Associação do Vitiligo com doenças infecciosas na cidade de Goiânia - Ribeiro, Rachel de Paula Santos (2017)
Autoimmune diseases can be triggered by viruses, bacteria and parasites. However, the participation of these infectious agents in the etiology of vitiligo, it is a current research topic. In this study, the serum of 51 participants with vitiligo and 51 control subjects was analyzed for the presence of anti-Toxoplasma gondii (T.gondii) IgG, anti-herpes simplex (HSV) 1/2 IgG, anti-cytomegalovirus (CMV) IgG and anti-hepatitis C (HCV) IgG.